An air-persistent oxyallyl radical cation with simple di(methyl)amino substituents. Issue 76 (2nd September 2016) - Regnier, Vianney; Molton, Florian; Philouze, Christian; Martin, David
Abstract : Despite minimal steric hindrance, the 1, 1, 3, 3-tetrakis(dimethylamino) oxyallyl radical cation is persistent for several hours in well-aerated solutions. Abstract : We report an experimental and theoretical study of the 1, 1, 3, 3-tetrakis-di(methylamino)oxyallyl radical cation. Despite simple substituents with minimal steric hindrance, this radical was found to be stable under an inert atmosphere and persistent for several hours in well-aerated solutions.